Banking in Globalisation: Commerzbank in the New Economic Course of the People’s Republic of China and the Role of Hong Kong - Liu Yi (Jahrbuch für Wirtschaftsgeschichte, 2023)
Since the open-up policy at the end of the 1970s, China – the largest single market in Asia – received growing attention from foreign investors and banks. However, the fragile domestic market and undeveloped financial system in China did not allow a rapid inflow of foreign banks, given that the foreign banks could exert suppression on the domestic banks. As a result, it took several years for most foreign banks to gain a foothold in mainland China. This article demonstrates how Commerzbank – one of the German Big Three – entered the Chinese market in the 1980s by establishing a branch in Hong Kong and opening a representative office in Beijing. On the basis of archival evidence and other contemporary sources, the case of China provides one slice of the history of Commerzbank’s expansion and illustrates how it coped with the surge of internationalisation in the 1980s.